A mixed model reduction method for preserving selected physical information. (1st March 2017) - Zhang, Jing; Zheng, Gangtie
Abstract: A new model reduction method in the frequency domain is presented. By mixedly using the model reduction techniques from both the time domain and the frequency domain, the dynamic model is condensed to selected physical coordinates, and the contribution of slave degrees of freedom is taken as a modification to the model in the form of effective modal mass of virtually constrained modes. The reduced model can preserve the physical information related to the selected physical coordinates such as physical parameters and physical space positions of corresponding structure components. For the cases of non-classical damping, the method is extended to the model reduction in the state space but still only contains the selected physical coordinates. Numerical results are presented to validate the method and show the effectiveness of the model reduction. Highlights: A mixed model reduction method in the frequency domain is presented for preserving physical information. Model reduction techniques from both the time and the frequency domain are combined. The dynamic model is condensed to selected physical coordinates only. Effective modal mass of virtually constrained modes are used to represent contributions of slave degrees of freedom.